PREVALENCE AND MANAGEMENT OF DYSMENORRHEA IN ADOLESCENT - Sukmawati Sukmawati; Intan Salsabila (Journal of Maternity Care and Reproductive Health, 2019)
Most adolescents who experience pain during menstruation make improper management such as consuming medicine from small stalls. It also lacks the use of non-pharmacological techniques to deal with the menstrual pain. This study aimed to determine the prevalence and treatment of dysmenorrhea in adolescent girls. The population in this study was year 7 and 8 students, totaling 127 students, the sample size used total sampling. Data collection used a questionnaire that has been tested for validity and reliability. Data analysis used univariate with distribution and frequency. The results showed that the highest level of menstrual pain was mild pain (82.7%), moderate pain (13.4%) and severe pain (3.9%). Handling dysmenorrhea with pharmacology mostly uses medicine from small stalls (69.7%) and the highest non-pharmacological treatment is drinking water (85.8%). It is expected that the school will work together with the Puskesmas to provid from small stalls, but they must be examined by health workers, immediately.Keywords : Dysmenorrhea, actions, Adolescents